Strength and creep testing for artificial ground freezing - Hampton, Christopher N. (1986)
Artificial ground freezing (AGF) provides a means by which excavations can be given temporary or permanent structural support. It may also be used to control the movement of groundwater without the risk of pollution of potable aquifers.